Analisis Kontribusi Keuntungan Atas Produk-Produk Pada Toko Kaca Dan Alumunium Ridho Utama Di Tenggarong (Penerapan Linear Programming Metode Simpleks) - Indrawan, Yudi; Iskandar, Iskandar; S, Syahhruddin (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2016)
The main objective of this study was to find out what is the optimum amount of production to generate maximum profit contribution for the products produced by Ridho Utama glass and Aluminum shop in Tenggarong. A series of observations carried out on the object of research is  Ridho Utama glass and Aluminum shop in Tenggarong where the company is going to take maximum advantage of two combinations of product that the product stove door (A3) and the product of the wardrobe (A8) with the respective number of optimal production was 7, 1883 or rounded up to 7 units and 33.215 or rounded to 33 units to generate the maximum profit of Rp 65,314,580, - or with rounded figure was Rp 64.750.000, for the glass installation-time or process 3 (S3) and mounting rubber or poccess 4 (S4) respectively still leave time for 590.1001 minutes it indicates that the company can save time on the 3 and 4 respectively during 590.1001 minutes or can be totaled 1180.2002 or 19,67 hours for 3 months. Another case for products that have the status of non basic or value equal to 0 (zero) it means that other product is better not manufactured by the company because it does not produce the maximum profit. Then the hypothesis has been stated previously that states "That the production of glass and Aluminum shop Ridho Utama in Tenggarong has been optimized so that produce the maximum profitKeywords: Profit Contributions(Application of Linear Programming Simplex Method)